The Effect of using Six Thinking Hats in Improving the Learning Motivation of Social Studies (A semi empirical study on the Sixth Basic Graders in Lattakia City) - Jnad, Rawha; Sultan, Manal; Jahjah, Reem Ghassan (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The present study aimed at knowing the level of learning motivation, and the effect of using Six Thinking Hats in improving it for the Sixth graders in Lattakia. The study was applied during the first time of the school year (2018\2019). The method of semi empirical was used, for that an educational program based on Six Thinking Hats method was designed for the third unit of the social studies book to the sixth grade. To measure the learning motivation Yousef Kattamy(1989) scale was used. The sample consisted of (60) students males and females, who distributed on two groups, the experimental was (30) and the control one was (30). . The study showed a decreasing in the level of learning motivation of the study sample and the results proved that using Six Hats method led to improve motivation of the experimental group, the differences were statistically significant at the level of (0.05) between the pre- and post tests. The results assured that there were statistical significant differences between the experimental and control groups in the post test in favor of the experimental group. The study led to recommendation of using Six Thinking Hats in teaching social studies subject and of applying more researches about it. هدف البحث الحالي إلى تعرف مستوى دافعية التعلم، وأثر قبعات التفكير الست في تحسينها لدى تلاميذ الصف السادس الأساسي في مدينة اللاذقية. حيث طبقت الدراسة خلال الفصل الأول من العام الدّراسي (2018/2019) واستُخدم فيها المنهج شبه التجريبي, ووفقاً لذلك تمّ تصميم برنامج تعليمي وفق طريقة قبعات التفكير الست للوحدة الثالثة من كتاب الدراسات الاجتماعية للصف السادس الأساسي. ولقياس دافعية التعلم تم الاعتماد على مقياس يوسف قطامي(1989)، وتكونت العينة من(60) تلميذاَ وتلميذة موزعين في مجموعتين تجريبية (30) وضابطة (30). أظهرت نتائج الدراسة انخفاض مستوى دافعية التعلم لدى عينة البحث، وتوصلت إلى أنّ استخدام قبعات التفكير الست أدى إلى تحسن الدافعية لدى المجموعة التجريبية، حيث كان الفرق دالاً إحصائياَ عند مستوى الدلالة (0.05) بين التطبيقين القبلي والبعدي، كما أكدت وجود فرق دال إحصائياً بين المجموعتين التجريبية والضابطة في التطبيق البعدي لصالح المجموعة التجريبية. واقترحت الدراسة استخدام طريقة القبعات الست في تعليم الدراسات الاجتماعية، وإجراء مزيد من الأبحاث حولها.